2020
DOI: 10.20944/preprints202009.0229.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong>Low-dose Whole-lung Irradiation for COVID-19 Pneumonia: What is the Optimal Dose? Final Results of a Pilot Study</strong>

Abstract: Purpose: Novel coronavirus disease (COVID-19) is the current global concern. Radiotherapy (RT), commonly employed in cancer management, has been considered one of the potential treatments for COVID-19 pneumonia. Here, we present the final report of the pilot trial evaluating the efficacy and safety of low-dose whole-lung irradiation (LD-WLI) in patients with COVID-19 pneumonia. Methods and Materials: We enrolled patients with moderate COVID-19 pneumonia who were older than 60 years. Participants were treated w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…The findings presented support recent demonstrations of positive clinical responses to LDRT in COVID-19 pneumonia patients [6] , [7] , [8] , [9] , [10] , [11] , [12] . However, animal studies also provide support for the effectiveness of Nrf2 in protecting various tissues from pro-inflammatory challenges.…”
Section: Nrf2 Activation Protects Against Covid-19 Pneumonia Ards and Other Inflammatory Diseasessupporting
confidence: 89%
“…The findings presented support recent demonstrations of positive clinical responses to LDRT in COVID-19 pneumonia patients [6] , [7] , [8] , [9] , [10] , [11] , [12] . However, animal studies also provide support for the effectiveness of Nrf2 in protecting various tissues from pro-inflammatory challenges.…”
Section: Nrf2 Activation Protects Against Covid-19 Pneumonia Ards and Other Inflammatory Diseasessupporting
confidence: 89%
“…] cite the Iranian study, and declare that their concept "clearly explains why Ameri et al concluded that 0.5 Gy was more effective than 1.0 Gy". This was not a conclusion of the study's authors, who address important limitations in their paper [4]. We cannot exclude that a different outcome would have been observed in our study with use of a lower radiation dose.…”
Section: Separating Evidence From Opinion -In Regards To [Xxx] Et Almentioning
confidence: 57%
“…Our trial was borne out of a clinical need, and we chose a randomized double-blind design to reduce any potential bias. The availability of prospective controls is the crucial difference between our study and earlier reports [4,7,8], a difference which [XXX-et-al. ] unfortunately did not consider as a source of discrepancy between results.…”
Section: Separating Evidence From Opinion -In Regards To [Xxx] Et Almentioning
confidence: 72%
“… 2 Studies have reported that SARS-CoV-2 spreads mainly through respiratory droplets and aerosols. 3–8 These respiratory droplets can be exhaled during coughing, sneezing, or even talking. 9 …”
Section: Introductionmentioning
confidence: 99%